Pembuatan dan Pengelolaan Website Desa Sebagai Media Informasi dan Administrasi Desa Kawisrejo - Khoiron, Mohamad; Alfani, Syahrul (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2024)
The writer wants to provide solutions and innovations to facilitate village administrative activities and access village information in Kawisrejo Village. The author provides the application of technology in Kawisrejo Village by creating a village website which contains village history, village information, village structure, and community services which will later be useful for administrative administrators as admins and the community as users of information and services. This implementation method will be divided into several stage, including the preparation stage, the implementation stage, and the evaluation stage. With the existence of a village website, the village can use it as an information medium and as a website-based village administration media. By making this website, it is hoped that Kawisrejo Village can solve problems in the exchange and delivery of information and promotions can be minimized easily and quickly.